Impact of age on outcomes of allogeneic hematopoietic stem cell transplantation with reduced intensity conditioning in elderly patients with acute myeloid leukemia. Issue 3 (11th January 2016) - Aoki, Jun; Kanamori, Heiwa; Tanaka, Masatsugu; Yamasaki, Satoshi; Fukuda, Takahiro; Ogawa, Hiroyasu; Iwato, Koji; Ohashi, Kazuteru; Okumura, Hirokazu; Onizuka, Makoto; Maesako, Yoshitomo; Teshima, Takanori; et al.
Abstract : Previous studies have repeatedly reported that increasing age is a significant risk factor for worse outcomes after allogeneic hematopoietic stem cell transplantation (allo‐HSCT) among patients with acute myeloid leukemia (AML). However, more recent studies reported conflicting results regarding the association between age and outcomes in elderly patients. Therefore, we conducted a large‐scale, nationwide retrospective study to examine the impact of age on outcomes of allo‐HSCT with reduced intensity conditioning (RIC) for AML patients who were older than 50 years. Of the 757 patients, 89 patients (11.8%) were 50–54, 249 patients (32.9%) were 55–59, 301 patients (39.8%) were 60–64 and 118 patients (15.6%) were ≥65 years old. The 3‐year overall survival (OS) (47.8, 45.2, 37.9, and 36.6% for patients aged 50–54, 55–59, 60–64, and ≥65 years, respectively, P  = 0.24) and nonrelapse mortality (NRM) (24.0, 22.8, 29.2, and 27.6% for patients aged 50–54, 55–59, 60–64, and ≥65 years, respectively, P  = 0.49) were not significantly different among the four age groups. Multivariate analysis revealed that increased age had no significant effect on OS or NRM after adjusting for covariates. These results suggested that advanced patient age is not a contraindication for RIC allo‐HSCT in elderly AML patients. Am. J. Hematol. 91:302–307, 2016. © 2015 Wiley Periodicals, Inc.